STRATEGI GURU AKIDAH AKHLAK DALAM MENINGKATKAN SELF CONTROL SISWA KELAS VIII MELALUI KEGIATAN PONDOK PESANTREN DI MTS NURUL ULUM PUTRI KEBONSARI MALANG - Khoirun Nisa; Eko Setiawan; Muhammad Sulistiono (VICRATINA, 2022)
Self control is self control, controlling attitudes and behavior. Self control needs to be built in students, so that they have awareness in controlling themselves from unwanted things. In line with the development of the times, many influences that change the habits of life. So that self-control must be improved to keep students wellbehaved and avoid negative influences. The objectives of this study are: (1) To describe how the strategy of the teacher of morals in improving student self-control at MTs Nurul Ulum Putri Kebonsari Malang, (2) To describe the results achieved from the strategy carried out on student self-control at MTs Nurul Ulum Putri Kebonsari Malang. This type of research is a field research that uses a qualitative approach with a descriptive qualitative analysis type of research. The results of this study include: (1) The strategy of teachers of moral aqidah in improving students' self-control at MTs Nurul Ulum Putri Kebonsari Malang, namely by applying the 5S culture (Smile, Greet, Greeting, Polite, Polite), coordinating with parents, teaching with attractive, set a good example, organize religious activities. (2) The results achieved from the strategy carried out on students' self-control are being calmer, disciplined and diligent as well as being more responsible.